A novel loss-of-function SYCP2 variant causes asthenoteratozoospermia in infertile males - Liu, Cong; Zhang, Yinfeng; Zhao, Youming; Luo, Haining (Frontiers in Genetics, 2025)
Background:Infertility is a multiplex disorder in the reproductive system. Unexplained infertility affects 2%-3% of reproductive-aged couples. Male factors contribute to about half of all infertility cases. About 15% of these cases are predicted to have a genetic etiology. With the wide application of whole exome sequencing (WES), more and more variations in male infertility have been identified.Methods:A patient diagnosed with asthenoteratozoospermia was involved in this study. WES was performed in the patient, and Sanger sequencing was used to confirm the variation. Mini-gene splicing assays were performed to validate the effect on the alternative splicing of the variation.Results:A novel heterozygous splice variant was identified in SYCP2 (c.2600+ 5G>C) in the patient ,which inherited from his phenotypically normal mother. SYCP2 encodes a protein critical for the synapsis of homologous chromosomes during meiosis I, and its disruption can impair spermatogenesis. Mini-gene splicing assays confirmed that this splicing variant impacted alternative splicing and that the stop codon appeared early, which was very likely to result in the loss of function of the protein and lead to the occurrence of male infertility.Conclusion:Our results suggested that the c.2600+5G>C variation in SYCP2 might be the genetic etiology for male infertility in this pedigree. This finding expanded the known genotype spectrum of male infertility and provided new etiological information for male infertility.